IMPROVING THE PROFESSIONAL INTERACTION OF HEALTHCARE PROFESSIONALS TO OPTIMIZE SPECIALIZED MEDICAL AND DRUG CARE FOR CANCER PATIENTS IN THE SYSTEM OF DRUG POLICY - Андрей Георгиевич Петров; Ольга Владимировна Хорошилова; Виктор Андреевич Семенихин; Сергей Николаевич Филимонов; Юлия Александровна Сашко (Медицина в Кузбассе)
It has been established that in the treatment and prevention of oncological diseases, the improvement of professional interaction of healthcare professionals in optimizing specialized medical and drug care for cancer patients in the system of drug policy is of particular importance. This situation requires continuity and feedback in the joint activities of medical and pharmaceutical workers, a constant increase in the level of interaction in all parts of the healthcare system.